The Online Marketing Strategic Planning for Jember Coffee SMEs - Oktalia Juwita; Fajrin Nurman Arifin; Fitriyana Dewi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2018)
Coffee is a kind of beverage that is widespread and much-loved in the world. Today coffee has become a lifestyle. Various kinds of coffee are offering in many shops. This is a great opportunity for entrepreneurs, especially SMEs providers of coffee products, in introducing and marketing variants of coffee products that are owned at the national and international level. One of the problems often arises in the marketing of SMEs products is the lack of information and marketing access to potential markets. An effective and appropriate marketing strategy is needed, especially for SMEs producing coffee products. The research method is done by observation and interview to get primary and secondary data. After the data obtained, analyzed the current condition using SWOT analysis and then followed by strategy mapping using SOSTAC method. From the analysis that has been done, needed a website for the directory to introduce SMEs engaged in the production and sale of coffee in Besuki Raya area.